Epimesatines A–I, nine undescribed prenylated flavonoids with SPHK1 inhibitory activities from Epimedium sagittatum maxim. (October 2022) - Xie, Shuangshuang; Zeng, Mengnan; Zhang, Jingke; Liu, Juanjuan; Wei, Junjun; Wang, Ru; Li, Meng; Hao, Zhiyou; Ji, Baoyu; Zheng, Xiaoke; Feng, Weisheng
Abstract: Epimesatines A–I, nine undescribed prenylated flavonoids, along with ten known analogues, were isolated from the aerial parts of Epimedium sagittatum Maxim. The structures and absolute configurations of epimesatines A–I were determined using a combination of spectroscopic data, Rh2 (OCOCF3 )4 -induced electronic circular dichroism (ECD) experiments, ECD comparisons, and X-ray crystallography analysis. Epimesatines A and I displayed notable activities on the viabilities of human non-small cell lung cancer (NSCLC) A549 cells with IC50 values of 1.77 and 9.97 μM, respectively. Furthermore, epimesatines A and I significantly inhibited the expression of sphingosine kinase 1 (SPHK1) in A549 cells. In addition, none of these compounds showed obvious toxicity on normal human lung bronchial epithelial BEAS-2B cells. Graphical abstract: Nine undescribed prenylated flavonoids, named epimesatines A–I, were isolated from Epimedium sagittatum Maxim. Epimesatines A and I showed significant activities against SPHK1 in A549 cells. Image 1 Highlights: Nineteen prenylated flavonoids including nine undescribed ones were isolated. Their absolute configurations were determined by Rh2 (OCOCF3 )4 -induced ECD experiments and X-ray crystallography analysis. The complete NMR data of 5, 7-dihydroxy-4′-methoxy-8-prenylflavonoid and honyucitrin were reported herein for the first time. Epimesatines A and I s ignificantly inhibited the expression of SPHK1 in A549 cells.